Electrical anisotropy of conductive structures in Earth’s crust of Red River fault Zone - Tuyến, Đoàn Văn; Toàn, Đinh Văn (Vietnam Journal of Earth Sciences, 2018)
Two tests for the electrical anisotropy hypothesis are introduced, evaluating the different features of magnetotelluric (MT) phases along measured profile. An analysis of MT field data on the line Hoa Sinh - Sac Ninh crossing Red River Fault Zone (RRFZ) Jets us devide five conductive structures at depth varying from 0.5 to 80 km. Only deeper one from them is indicating high electrical anisotropy may be related to the evidence of Lithosphere activity beneath RRFZ. Other structures are isotropic distributing in the crust out site RRFZ related to high conductive mineral and hot water sources.